The impact of determinants intellectual capital on organizational citizenship behavior of village apparatus In improving community services - Deky Hamdani (Cita konsultindo, 2023)
This study aims to analyze the the impact of determinants intellectual capital on organizational citizenship behavior of village apparatus in improving community services and to analyze the direct impact and indirect impact on determinants intellectual capital on organizational citizenship behavior of village apparatus in improving community services. The novelty of this study is: to develop and formulate a model of determinants of intellectual capital through organizational citizenship behavior of village devices that have an impact on improving community services in Sungai Full City, where previous research only discussed intellectual capital from the company and employee sectors.This research using Structural Equation Modeling (SEM). Total sample of 117 respondents. The data used in this study were primary data through interviews and questionnaires. Data analysis in this study uses a structural equation model with the analysis tool used is to use AMOS. The results of this study : The Intellectual Capital can be explained by the variables Social Capital, Organizational Capital, Human Capital about 1,4%. While Organizational Citizenship Behavior can be explained by the variability of Social Capital, Organizational Capital, Human Capital and Intellectual Capital is 84,9%